Prosecutors’ perceptions of how to improve the quality of evidence in domestic violence cases - Westera, Nina J. (Policing and society, 2017)
Limited evidence in domestic violence prosecutions is a persistent problem. Focus groups with 13 prosecutors from across Australia and New Zealand were used to explore how to improve the quality of evidence collected and presented in these cases. A thematic analysis identified three main strategies: improving the quality of investigations by initial police responders, supporting the complainant and tailoring the trial process to the domestic violence context. The most discussed strategy within these categories has previously received little attention- police video recording the complainant's initial account and using that video as the basis for the complainant's courtroom testimony.